8-4(-7x+8)=11

Simple and best practice solution for 8-4(-7x+8)=11 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 8-4(-7x+8)=11 equation:


Simplifying
8 + -4(-7x + 8) = 11

Reorder the terms:
8 + -4(8 + -7x) = 11
8 + (8 * -4 + -7x * -4) = 11
8 + (-32 + 28x) = 11

Combine like terms: 8 + -32 = -24
-24 + 28x = 11

Solving
-24 + 28x = 11

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '24' to each side of the equation.
-24 + 24 + 28x = 11 + 24

Combine like terms: -24 + 24 = 0
0 + 28x = 11 + 24
28x = 11 + 24

Combine like terms: 11 + 24 = 35
28x = 35

Divide each side by '28'.
x = 1.25

Simplifying
x = 1.25

See similar equations:

| -0.01x^2+0.4x-20=0 | | 7x+8x-16=59 | | 150.99x+2625=4889.85 | | 175x^2-290x+120=0 | | z=2.4/3.8 | | 5-c=3/4 | | 17-x=-25-4x | | -13-[-9]+[-8]= | | -x-5=7-3x | | -19.7=-2.2 | | 6y^3-10y^2=4y | | 35x^2+46x-16=0 | | -(x+5)=14 | | 15-x=-5x-45 | | y=313-2 | | y+0.8x=0.4 | | 100p^2-100p-600=0 | | 6y-6x=6 | | 7+p=3 | | -5x-9=-6x+5 | | 2p-16=4(3-3p) | | u-9.2=7.21 | | 5x+1=29-3x | | 88x^2+17x-6=0 | | Z^2=3+2i | | 2y+(-5)=1 | | -3(1+6r)=1-r | | n^2+14n+45=0 | | -2k+7=13 | | 19+6p=-8 | | (8.2x+4)=6.7x+5.2 | | 10=9+x+21+(9+x) |

Equations solver categories